The Influence Of Perceptions Of Price, Product Quality, And Location, On The Decision To Purchase Alton Bintaro Jaya Cluster Housing - Marharatua Oktafio; Baruna Hadibrata (Dinasti International Journal of Management Science, 2024)
This research aims to test and analyze the influence of price, product quality, location and purchasing interest on Alton Cluster purchasing decisions as intervening variables. The type of research carried out in this research is causal associative research with quantitative techniques. The number of samples used was 105 respondents with the non-probability sampling technique used was purposive sampling. Data processing in this research uses researchers using IBM SPSS Statistics 26 software to analyze descriptive characteristics and SmartPLS 4 software to measure research data using the Partial Least Square (PLS) method. The results of this research show that price, product quality, location influence interest. buy the Alton Cluster House at PT. Jaya Real Property, This shows that the more suitable or affordable the price and location, the more interest in buying Alton Bintaro Jaya Cluster Houses will increase. Price, product quality, location influence the purchasing decision to buy an Alton Cluster House at PT. Bintaro Jaya, this shows that the more suitable or affordable the price and location, the greater the decision to purchase Alton Bintaro Jaya Cluster Houses. Purchase interest influences the decision to purchase Alton Cluster Houses at PT. Bintaro Jaya. This shows that the higher the buying interest, the greater the decision to purchase the Alton Bintaro Jaya Cluster House. Location influences the purchasing decision to buy an Alton Cluster House at PT. Bintaro Jaya, this shows that the more suitable or affordable the price and location, the greater the decision to purchase Alton Bintaro Jaya Cluster Houses. Purchase interest influences the decision to purchase Alton Cluster Houses at PT. Bintaro Jaya. This shows that the higher the buying interest, the greater the decision to purchase the Alton Bintaro Jaya Cluster House. Location influences the purchasing decision to buy an Alton Cluster House at PT. Bintaro Jaya, this shows that the more suitable or affordable the price and location, the greater the decision to purchase Alton Bintaro Jaya Cluster Houses. Purchase interest influences the decision to purchase Alton Cluster Houses at PT. Bintaro Jaya. This shows that the higher the buying interest, the greater the decision to purchase the Alton Bintaro Jaya Cluster House.